Sosialisasi Model Project Based Learning Berorientasi Budaya Lokal di Tingkat Sekolah Dasar - Ema Butsi Prihastari; Ratna Widyaningrum; Ifa Hanifa Rahman (Universitas Mathla'ul Anwar Banten, 2021)
SOCIALIZATION OF PROJECT-BASED LEARNING MODEL ORIENTED TO LOCAL CULTURE AT ELEMENTARY SCHOOL LEVEL. The goal achieved by the socialization of local culture-based project learning models is to provide teachers insights and skills in teaching with the Project-Based Learning model, which is model-oriented to learner's activities and independence and preserving local culture. It is realized in the learning tools PjBL model-oriented local culture that produces products. This service was conducted at SDN Nayu Barat 2 Surakarta with a target of 17 teachers to implement it. Methods of implementation of devotion include: a) participatory, b) awareness, c) learning (theory and practice), d) mentoring. While the mechanism of implementation of devotion include: a) preparation and b) implementation that includes the presentation of materials, the creation of learning devices with PjBL models, assignments, evaluation, and reflection that ends with the closure.